System Analysis of Dengue Virus Surveillance in BBTKL PP Surabaya Year 2012â2014 - Husnayain, Atina; Artanti, Kurnia Dwi; Zaenal, Acub (Jurnal Berkala Epidemiologi, 2015)
ABSTRACTChanging the distribution of dengue virus serotypes has occurred in Indonesia. This condition should be monitored continuously through the Dengue Virus Surveillance. Implementation of Dengue Virus Surveillance also conducted by BBTKL PP Surabaya. The purpose of this study was to determine the workflow, identify problems, set priority problem, find the cause of the problem, and provide the alternative solution related to problems of Dengue Virus Surveillance in BBTKL PP Surabaya. This is a operational research and the informants are officers of Dengue Virus Surveillance in BBTKL PP Surabaya. Data in this study was analyzed descriptive and presented narrative. Results showed that the workflow of Dengue Virus Surveillance in BBTKL PP Surabaya are collecting of patientâs blood and vector specimen, vector survey and collecting the supporting data, Rapid Diagnostic Test (RDT) and Polymerase Chain Reaction (PCR), processing and data analysis, and dissemination the information. The main problems of Dengue Virus Surveillance in BBTKL PP Surabaya is the low quality of the information. Tree problem analysis showed that the cause of problem that can be intervene are incomplete supporting data and data storage. Alternative solution related to problems of Dengue Virus Surveillance in BBTKL PP Surabaya is use of Epi Info.Keyword: surveillance, dengue virus, data management